SISTEM INFORMASI SIMPAN PINJAM PADA KOPERASI CEMPAKA WANGI JAMBI: Information System, Savings and Loans, Cooperative Cempaka Wangi jambi,PHP - Suana, Irma (LP2M Universitas Nurdin Hamzah, 2018)
The processing system of savings and loan at Cooperative/ KoperasiCempaka Wangi Jambi which has been running so far still uses manual system whose data is still stored in the ledger. Some formulation of the problems were put forward namely how did the process of data of savings and loan go?, with the aim to know how the prosess of data processing of savings and loan was going on and also to design a system that solved the problem in the processing of savings and loans in order to provide precise and fast information, and without any data concurrence. In this study the authors used library research, field research and performed analysis using Data Flow Diagram (DFD) as a tool. Data processing system of preparing reports that were expected were still less effective and efficient. Therefore the author tried to design a website-based information system to produce accurate and precise information so that it could assits the leader in making decisions. The purpose of making this thesis was to design a system of data processing of savings and loan to be more effective and efficient. As for its application, it is suggested that the first thing to be done is to find out the system that is running and the need for training and introduction to the cooperative party in order to understand the application program that will be applied.